2006
DOI: 10.1001/archpedi.160.11.1114
|View full text |Cite
|
Sign up to set email alerts
|

Iron Depletion Is Associated With Daytime Bottle-feeding in the Second and Third Years of Life

Abstract: In the second and third years of life, there is an almost 2-fold association between iron depletion and daytime bottle-feeding compared with cup feeding. The child's age may be a modifier, and milk volume consumed may be a mediator, of this association. Duration of bottle use is a potentially modifiable practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 28 publications
0
35
0
Order By: Relevance
“…[9][10][11][12] We did not find an association between serum non-HDL cholesterol concentration and the dietary intake subscore of the NutriSTEP questionnaire, which is consistent with other studies involving young children that have shown an association between eating behaviours (e.g., bottle use) and iron deficiency outcomes that were independent of dietary intake (e.g., milk volume). [21][22][23] These results raise the possibility that eating behaviours are more closely related to health outcomes than dietary intake. The relations between eating behaviours and LDL cholesterol and apolipopro-…”
Section: Discussionmentioning
confidence: 94%
“…[9][10][11][12] We did not find an association between serum non-HDL cholesterol concentration and the dietary intake subscore of the NutriSTEP questionnaire, which is consistent with other studies involving young children that have shown an association between eating behaviours (e.g., bottle use) and iron deficiency outcomes that were independent of dietary intake (e.g., milk volume). [21][22][23] These results raise the possibility that eating behaviours are more closely related to health outcomes than dietary intake. The relations between eating behaviours and LDL cholesterol and apolipopro-…”
Section: Discussionmentioning
confidence: 94%
“…Previous research has identified an association between prolonged use of bottle-feeding and Fe deficiency (31)(32)(33) . Overweight, obesity, wheezing and dental caries have also been found to be associated with prolonged bottle-feeding and bedtime bottle use (34)(35)(36)(37)(38)(39) .…”
Section: Discussionmentioning
confidence: 99%
“…Unmodified cow's milk increases intestinal blood loss in infants [5], while bottle feeding contributes to the risk independently, probably due to the greater volume of cow's milk consumed [6]. 3.…”
Section: Dietary Factorsmentioning
confidence: 99%